Efektivitas Inquiry-Based Learning untuk Meningkatkan Motivasi Belajar Siswa Kelas XI di SMAN 9 Padang - Muhamad Rajab Siregar (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to identify whether the application of Inquiry-Based Learning in learning tolerance material in Islam can increase the learning motivation of class XI students at SMAN 9 Padang, and to find out what factors affect the effectiveness of the use of this model. It is expected that the results of this study can make a significant contribution in an effort to improve the quality of learning in schools, especially in increasing student motivation to learn the material taught. This research uses Classroom Action Research (PTK) which aims to improve the quality of learning in the classroom by designing, implementing, and evaluating actions repeatedly to improve or improve ongoing learning practices. The population in this study were all grade XI students enrolled in SMA Negeri 9 Padang in the 2023/2024 school year totaling 300 students who took Islamic Religious Education subjects. The sample in this study was taken by purposive sampling, namely choosing a class that was in accordance with the research objectives. The sample selected was one class from a group of grade XI students who had a low level of learning motivation or were in a condition that needed improvement. This sample amounted to about 30-35 students. Based on the results of the research conducted through three cycles of Inquiry-Based Learning implementation, it can be concluded that this learning model is effective in improving learning motivation